Biodegradable Nanocomposite Poly(Lactic Acid) Foams Containing Carvacrol-Based Cocrystal Prepared by Supercritical co2 Processing for Controlled Release in Active Food Packaging - Romero-Figueroa, J; Galotto-Lopez, M; Torres-Mediano, A; Riveros-Faba, S (Elsevier B.V., 2024)
Compounds derived from essential oils have been used in active packaging, but their volatility and degradability negatively affect stability and leads to high release rates. The present study aimed to develop PLA bionanocomposite foams loaded with carvacrol cocrystal by supercritical CO2 and its release into a food simulant for control release in food packaging. For this purpose, 4,4′-bipyridine was used as coformer and carvacrol as active agent. Cocrystallized closed cell foams were obtained using supercritical CO2 and were characterized in terms of their physicochemical and mechanical properties, and release kinetics to a D1 simulant were evaluated as well as the antioxidant ability. A better overall mechanical behavior due to the nanoclay promoting a higher interfacial adhesion with the polymeric matrix was revealed. A higher incorporation of carvacrol was observed in samples with higher C30B content. The incorporated cocrystals showed a decrease of one order of magnitude in the estimated effective diffusion coefficient of carvacrol and showed antioxidant activity. These results suggest that the nanocomposite foam containing carvacrol-based cocrystals could be used in active packaging systems with controlled release characteristics, especially with highly volatile compounds, and can be proposed for other fields such as biomedical applications. © 2023